2009
DOI: 10.2106/jbjs.h.00191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroids on the Biomechanical Strength of Rat Rotator Cuff Tendon

Abstract: A single dose of corticosteroids significantly weakens both intact and injured rat rotator cuff tendons at one week. This effect is transient as the biomechanical properties of the steroid-exposed groups returned to control levels by three weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 38 publications
6
83
2
4
Order By: Relevance
“…On the other hand, Hossain et al 26 showed that induction of apoptosis was observed in tenocytes when 25 and 50 mg/ml doses of dexamethasone were administered. In an in vivo study, Mikolyzk et al 27 reported that steroids reduced the biomechanical properties of rotator cuff tendons. However, the deleterious effect of corticosteroids on the biomechanical properties of the exposed supraspinatus tendon was temporary, and the properties of these tendons returned to control levels in 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hossain et al 26 showed that induction of apoptosis was observed in tenocytes when 25 and 50 mg/ml doses of dexamethasone were administered. In an in vivo study, Mikolyzk et al 27 reported that steroids reduced the biomechanical properties of rotator cuff tendons. However, the deleterious effect of corticosteroids on the biomechanical properties of the exposed supraspinatus tendon was temporary, and the properties of these tendons returned to control levels in 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The corticosteroid injection soon after the baseline tests resolved the joint effusion in our participant, and thereby improved the mechanical conditions for recovery of the tendon-muscle complex. However, there are also reports on adverse effects of local corticosteroid injections on tendon strength, but this may be transient (16).…”
Section: Discussionmentioning
confidence: 99%
“…Mikolyzk and colleagues [2] showed a maximal load decrease of 27% and a stiffness decrease of 32% in intact uninjured tendons after a single injection. The study by Maman and colleagues [1] demonstrated a noteworthy decrease in the strength of normal uninjured rat rotator cuff tendon 1 week after exposure to repeated corticosteroid injections.…”
Section: Corr Insightsmentioning
confidence: 96%
“…More recent studies [1,2] investigated the biomechanical effects of corticosteroid exposure on both uninjured and injured rotator cuff tendons in rats. Mikolyzk and colleagues [2] showed a maximal load decrease of 27% and a stiffness decrease of 32% in intact uninjured tendons after a single injection.…”
Section: Corr Insightsmentioning
confidence: 99%